Renewable Energy : Power for a sustainable future - Boyle, Godfrey; Open University (Oxford : Oxford University Press, 2012)
This title examines the practical and economic potential of renewable energy sources to provide sustainable energy. The underlying physical and technological principles of these sources are examined within the context of their environmental impacts, economics and future prospects.
Published in association with the Open University.
Includes bibliographical references and index.
Keywords: Renewable energy sources; Environment and Ecology